MATHEMATICAL MODEL OF CURRENT CAPITAL’S OPTIMIZATION AND MANAGEMENT - Hryniuk, Iryna (Acta Universitatis Nicolai Copernici. Zarządzanie, 2019)
Current capital management is an important part of the enterprise management system. Determining the optimal value of its components allows more effectively using assets and investing resources. In order to determine the optimal value, it is necessary to determine the basic interdependence between these components. The process of optimization is based on the relationships and interactions between the components of current capital. The mathematical model of optimization of current capital components has been formed and proposed for the purpose of determining the optimal value of each of the components, which will enable the company to more effectively use available resources and production capacities and prevent inappropriate spending and investment of resources. This model is based on the Lotka–Volterra equations and represents a system of three differential equations that describe the interactions and interdependencies between the components of current capital, determining their optimal size, which ensures the continuity of economic activity, in the use of all production capacities of the enterprise and will help to prevent inefficient spending and investment in assets. The model is created in the process of PhD thesis writing.